Money Velocity and Asset Prices in the Euro Area - Christian Dreger; Jürgen Wolters (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Monetary growth in the euro area has exceeded its target since several years. At the same time, the money demand function seems to be increasingly unstable if more recent data are used. If the link between money balances and the macroeconomy is fragile, the rationale of monetary aggregates in the ECB strategy has to be doubted. In fact, a rise in the income elasticity after 2001 can be observed, and may reflect the exclusion of real and financial wealth in conventional specifications of money demand. This presumption is explored by means of a cointegration analysis. To separate income from wealth effects, the specification in terms of money velocity is preferred. Evidence for the presence of wealth in the long run relationship is provided. In particular, both stock and house prices have exerted a negative impact on velocity after 2001 and lead to almost identical equilibrium errors. The extended error correction model is stable over the entire sample period and survive a battery of specification tests.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: C22; C52; E41; 330; Cointegration analysis; error correction; money demand; financial wealth; monetary policy